2018
DOI: 10.1097/md.0000000000010799
|View full text |Cite
|
Sign up to set email alerts
|

Total spondylectomy of recurrent giant cell tumors in the cervical spine

Abstract: Rationale:Spinal Giant Cell Tumors (SGCTs) are rare, aggressive, and benign tumors. Their presence in the cervical spine is even more exceptional. There are few reports of cervical GCT in the literature, especially recurrent cases. The treatment are challenging to clinically because radical resection is extremely difficult.Patient concerns:In this study, we present the cases of a 25-year-old man and a 41-year-old woman who suffered from recurrent cervical GCT.Interventions:They underwent extensive total spondy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…In general, local radiation, denosumab, or bisphosphonate can be used as adjuvant treatments after partial or subtotal resection of cervical GCT (Table 1). 1,2,[8][9][10][11][12][13] Radiation is administered as an adjuvant treatment to prevent postoperative recurrence in cases in which complete resection is difficult, but its efficacy is still controversial. 14,15) It has also been reported that myelopathy and radiationinduced sarcoma may develop due to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In general, local radiation, denosumab, or bisphosphonate can be used as adjuvant treatments after partial or subtotal resection of cervical GCT (Table 1). 1,2,[8][9][10][11][12][13] Radiation is administered as an adjuvant treatment to prevent postoperative recurrence in cases in which complete resection is difficult, but its efficacy is still controversial. 14,15) It has also been reported that myelopathy and radiationinduced sarcoma may develop due to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Giant cell tumor of bone (GCTB) usually appears as a benign tumor with local aggressiveness. [ 1 ] Malignant giant cell tumor of bone (MGCTB) is rare and is currently described as either primary or secondary. Only a few cases have been described in the literature to date.…”
Section: Introductionmentioning
confidence: 99%
“…Заболеваемость опухолями в подвижном отделе позвоночника (выше крестца) колеблется от 1,4 до 9,4 %, а вовлечение шейного отдела позвоночника происходит еще реже [7]. Несмотря на доброкачественную природу опухоли, локально она может быть агрессивной и иметь метастатический потенциал [8].…”
unclassified